THE IMPACT OF EDUCATIONAL STAKEHOLDERS' ATTITUDES ON STUDENTS' ACADEMIC AND CAREER INTERESTS IN CERAMICS WITHIN THE KUMASI METROPOLIS, GHANA - James, Nuako Jerry; Agyei, Isaac Kwabena; Fening, Peggy Ama; Joe, Adu-Agyem; Adjei, Kofi (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2024)
Educational programmes whether vocational or not have the potential to shape students to be able to give back to their societies. Unfortunately, some attitudes of players of education can affect students so much to dampen their self-efficacy and interest in Ceramics education. This study investigated some educational stakeholders' and their attitudes that can possibly have negative impact on students' academic and career interest in Ceramics within the Kumasi Metropolis, Ghana. Three schools offering Ceramics in the metropolis were purposively selected. They consisted of one mixed-gender, one boys-only, and one girls-only schools. The study was exploratory research and adopted the QUAN+Qual mixed-methods triangulation to conduct the investigation. Data was concurrently gathered using questionnaire, interviews and observation. 273 participants, including students, teachers, schools’ heads and parents were sampled from the three selected schools. Four Likert scale questionnaire and “Yes or ‘No’ data type was employed where SPSS v24, excel spreadsheet applications as well as frequencies and percentages (descriptive statistical techniques) helped to simplify and interpret the data. The study's findings revealed that educational stakeholders such as parents, students and their peers, teachers and schools’ managers put up behaviours that discourage students’ interest in Ceramics. The study found that low employment opportunities in Ceramics is the primary reason why parents, students, and teachers discourage students’ academic and career interest in Ceramics. The study also conducted a chi-square to establish whether the age, programme and level in school had any correlation with their believe that there is a low employment opportunity in Ceramics. The results found that the level of students alone to have significant correlation with p>0.000.